The evaluation of cyclin D1 expression in prostate carcinoma cases - Aksoy, Asude; Vicdanli, Selcen; Artas, Gokhan (Kare Publ, 2024)
OBJECTIVE: Cyclin D1 (CDDN1) is an important protein for mitotic cell cycle advancement through the G1 phase and contributes to the control of the cyclin-dependent kinases CDK4 and CDK6. We evaluated the relationship between CDDN1 expression and clinicopathological features in prostate cancer (PCa) cases and whether CDDN1 could be used as a prognostic biomarker for PCa cases in this study. METHODS: This study comprised ninety cases; seventy-five had PCa and fifteen had benign prostatic hypertrophy (BPH) diagnoses (as the control group). The pathological specimens were stained immunohistochemically and categorized as a 'low' (L) or a 'high' (H) group for CDDN1 expression. The cases' clinicopathological features and survival rates were evaluated statistically, within a 95% confidence interval, p<0.05, retrospectively. RESULTS: The median follow-up time was 75 (17-96) months, and the median overall survival (OS) was 87 months (CI 95%: 74.74-99.25). While the OS was 66 months (CI 95%: 49.61-82.38) in the H-CDDN1 group, the OS of the L-CDDN1 group was not yet reached. The OS of the L-CDDN1 group was longer in statistical significance (p=0.011). A Cox regression analysis revealed that the levels of CDDN1 expression, the values of lactate dehydrogenase, and post-treatment prostate specific antigen were found to be prognostic factors for OS in PCa cases (p<0.05). CONCLUSION: Our results suggest the overexpression of CDDN1 is a potentially useful but poor prognostic biomarker for PCa cases.
Prostat kanseri hastalarında siklin D1 ekspresyonunun değerlendirilmesi
Keywords: Biomarker; cyclin D1; prognosis; prostate carcinoma; survival